Telephones, Narrative, Algorithms: Untimely Meditations on Kafka - Ansgar K. Mohnkern (Humanities)
This essay traces Kafka’s writings as documents of a technological consciousness both a century ago and today. On the one hand, they are historical archives indexing the influence of modern technology in the lifeworld of the early 20th century. On the other hand, however, they also carry a historical index through which they become precise informants of our digital age. With a particular eye on Kafka’s parable “Before the Law”, this essay carves out elements of a narrative order which, as for surprising formal correspondences, can (and perhaps must) be called algorithmic.